THE INFLUENCE OF FINANCIAL PERFORMANCE ON THE STABILITY OF ISLAMIC COMMERCIAL BANKS IN INDONESIA WITH GREEN BANKING AS A MODERATING VARIABLE - Karmila, Maya (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2025)
Financial performance in general is an important aspect in evaluating the financial stability of a bank. Banks involved in green banking activities tend to have a better reputation because they show concern for environmental issues. This study aims to analyze the effect of financial performance on the stability of Islamic banks with green banking as a moderating variable. The financial performance indicators used include the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Operating Expenses to Operating Income (OEOI), and Financing to Deposit Ratio (FDR). The population in this study consisted of 14 Islamic commercial banks. The sample selection used the nonprobability sampling method with a purposive sampling technique and obtained a sample of 10 Islamic commercial banks with a research period of 2020–2023, so that there were 40 research data. The analysis was carried out using panel data regression with the Random Effect Model (REM) approach and variable moderation tests using Moderated Regression Analysis (MRA) through the Eviews 12 program. The results showed that CAR had a significant positive effect on stability, FDR had a significant negative effect on stability, while NPF and OEOI had no effect on stability. Green banking weakens the influence of CAR and NPF on stability, strengthens the influence of FDR on stability, but does not moderate the influence of OEOI on stability. This shows that the role of green banking is quite good, but has not been able to improve all aspects of financial performance as a whole.